On-site and off-site impact of watershed development: a case study of Rajasamadhiyala, Gujarat, India - Sreedevi, T.K.; Wani, S.P.; Sudi, R.; Patel, M.S.; Talati, Jayesh; Singh, S.N.; Shah, Tushaar (International Crops Research Institute for the Semi-Arid Tropics, 2006)
Detailed case study of Rajsamadhiyala watershed in the semi-arid tropical area of Gujarat in India revealed that rainwater harvesting through watershed management doubled the productivity of groundnut and other major crops, increased cropping intensity by 32% in eight years. With improved groundwater availability diversification with high-value crops like cumin, vegetables and fruits was observed. Food, fodder, fuel sufficiency substantially improved along with the increased incomes, literacy and social development. Substantial investment of 16.25 million rupees (US$ 0.36 million) in rainwater harvesting in one village created storage capacity to harvest 16% of mean annual rainfall of 503 mm which is equivalent to 100% of potential runoff during a normal year. Considering percolation seepage and evaporation losses 40% of annual mean rainfall could be harvested and stored. However, because of geological formation in the Deccan plateau where soils are formed over a layer of weathered trap laid on hard rock during normal rainfall years, these structures overflow 2-3 times in the rainy season. Downstream villages Aniyala and Katurba Dham benefited in terms of increased groundwater availability, reduced siltation and flooding through the base flow seepage water and excess runoff. Detailed studies in two downstream villages showed increased productivity, however, by 25-30%, improved groundwater availability by 25%, and reduced distressed migration. Dedicated leadership helped the villagers to chalkout the path to prosperity. Vast potential to increase productivity by 80-90% remains to be harnessed through adoption of increased water use efficiency measures, as most benefits are due to increased water availability only. However, looking at the trends of over-exploitation of groundwater by doubling the number of borewells and pumping hours call for urgent steps to develop suitable social/legal mechanisms for sustsainable use of water resources through integrated water resource management. Improved water availability through public investment triggered private/individual investment in agriculture in rainfed areas further hastening the process of development.